D. H. Lawrence’s The Rainbow: A Critique of Social Pornography - Al-Farttoosi , Tahseen Ali Mhodar (International Journal of Psychosocial Rehabilitation, 2020)
This paper tries to examine the depiction of social corruption in D. H. Lawrence’s The Rainbow (1915). The study will focus on the portrayal of the social perspective upon the issue of pornography and its literary manifestation in the selected novel. Pornography was a kind of social taboo in the first decades of the nineteenth century. That is, pornography, especially in England, was not accepted at all social scales. Yet, it began to occupy the social circumferences by the advent of the twentieth century, the social attitudes towards pornography drastically changed. People began to be accustomed to the flagrant pornographic issues at the time. Consequently, people resented this kind of pornographic attitude. They reacted to its spread in the society in different ways. Lawrence, therefore, uses his novel as a means of critiquing the reality of pornography. In so doing, he attempts to amend such social flaw in the course of his fictional depiction. The study will apply a narrative theory to explore the realistic insights in Lawrence’s fictional plot. Therefore, Patrick O’Neill’s concept of projection will be applied to identify this reality.